Prinsip-Prinsip Pendidikan Anak Dalam Ulangan 6:4-9 - Sri Astuti; Desi Sutresia Silalahi (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
The problem in this paper lies in the principles of child education contained in the Israel Shema. This discussion aims to First, the author can find out how the Israeli concept of children and the significance of children's education for the Israelites; Second, the writer knows the method or method applied by Israeli parents in educating their children; Third, the author can explore and describe the principles of child education contained in Deuteronomy 6:4-9. So this paper uses a library research approach. The conclusion of this paper proves that first, first, the nation of Israel is a nation that prioritizes education for children, because for the Jewish nation children are a precious gift from God. Second, in the Jewish tradition the family is the first and foremost place of education for children. The pattern used by Israeli parents in educating their children is by bringing their children to attend worship rituals, namely religious activities in houses of worship or celebrating religious holidays with the family, so that children have direct experience with God through worship, as well as using symbols. In addition, the methods used are verbal and non-verbal methods. Third, three important things are the principles of Shema written in Deuteronomy 6:4-9, namely loving God, educating children is the responsibility of parents, and repeated teaching. Abstrak Bahasa Indonesia Permasalahan dalam tulisan ini terletak pada Prinsip-prinsip pendidikan anak yang terkandung dalam Shema Israel. Pembahasan ini bertujuan untuk Pertama, penulis dapat mengetahui bagaimana konsep orang Israel tentang anak dan signifikansi pendidikan anak bagi bangsa Israel; Kedua, penulis mengetahui cara atau metode yang diterapkan oleh orangtua Israel dalam mendidik anak; Ketiga, penulis dapat menggali dan menguraikan prinsip-prinsip pendidikan anak yang terkandung dalam Ulangan 6:4-9. Maka tulisan ini menggunakan pendekatan penelitian kepustakaan. Kesimpulan tulisan ini membuktikan bahwa pertama, Pertama, bangsa Israel merupakan bangsa yang sangat mengutamakan pendidikan kepada anak, sebab bagi bangsa Yahudi anak adalah anugerah berharga dari Allah. Kedua, dalam tradisi Yahudi keluarga merupakan tempat pendidikan pertama dan yang utama bagi anak. Pola yang digunakan orang tua Israel dalam mendidik anak yaitu dengan membawa anak untuk mengikuti ritual ibadah, yaitu kegiatan keagamaan di rumah ibadah maupun merayakan hari raya keagamaan bersama keluarga, sehingga anak memiliki pengalaman langsung dengan Allah melalui ibadah, juga menggunakan simbol-simbol. Selain itu, metode yang digunakan adalah metode verbal dan non verbal. Ketiga, tiga hal penting yang menjadi prinsip pendidikam Shema yang tertulis di dalam Ulangan 6:4-9, yaitu mengasihi Allah, pendidikan anak adalah tanggung jawab orang tua, dan pengajaran berulang-ulang.